A Note on the Fixed Point of Generalized Eventual Cyclic Gross Contractive Mappings - Jin Liang; Sheng-Hua Yan (Journal of Function Spaces and Applications)
Based on the work of Agarwal et al., in press, we introduce a concept of generalized eventual cyclic gross contractive mapping in metric spaces, which is a generalization of the eventual cyclic gross contractions. Furthermore, we analyze the existence of a fixed point for this type of contractive mapping, and present a new and general fixed point theorem.